Ensiklopedi tanaman obat Indonesia - Haryanto, Sugeng ([Yogyakarta] : Palmall, 2009)
Encyclopedia of medicinal plants for traditional herbal medicine in Indonesia.
Keywords: Medicinal plants -- Indonesia -- Encyclopedias; Herbs -- Therapeutic use -- Indonesia -- Encyclopedias; Traditional medicine -- Indonesia -- Encyclopedias